INTERCULTURAL TASKS FOR GLOBAL COMMUNICATION SKILLS - Kalayo Hasibuan; Yulia Stevani; Nursyahfitri H; Khoiri Alhabsy; Alia Riska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Intercultural communication skills are increasingly important in the modern global era because people from different cultural backgrounds interact more frequently in education, business, technology, and social life. This paper discusses the implementation of intercultural tasks as a strategy to improve students’ global communication skills. Intercultural tasks refer to learning activities that encourage students to understand, respect, and communicate effectively with people from diverse cultures. The study uses a qualitative descriptive method by reviewing several educational practices and theories related to intercultural learning. The findings show that intercultural tasks help students develop communication competence, cultural awareness, empathy, collaboration, and critical thinking. Activities such as cultural discussions, role plays, online collaboration, presentations, and international projects provide opportunities for learners to practice real-life communication in multicultural contexts. In addition, students become more confident in expressing opinions and understanding cultural differences positively. The discussion highlights that teachers play an important role in designing meaningful intercultural activities that support active participation and open-minded attitudes. Therefore, intercultural tasks can be considered an effective approach to preparing students for global interaction and communication in the twenty-first century.